Primary cervical lymphoma: a rare presentation to a genitourinary medicine clinic. (July 2013) - Bull, L; Knowles, A; Ogden, S; Boag, F; Naresh, K N; Bower, M
Summary: Primary non-Hodgkin's lymphoma of uterine cervix is a rare diagnosis. We present the case of a 47-year-old woman who presented to our genitourinary (GU) medicine service complaining of a malodorous discharge. Speculum examination revealed a necrotic mass on the cervix. She was referred urgently to gynaecology and subsequent histology revealed a diffuse large B-cell lymphoma. She received six cycles of RCHOP chemotherapy and is now in clinical remission. This case highlights the need for GU medicine physicians to remain vigilant with regard to possible gynaecological malignancies in all of our patients, the need for medical backup within GU medicine clinics and for clear pathways of referral to other specialists to exist.